The impact of government-sponsored poverty eradication programmes in Lundu district, Kuching division, Sarawak - Lim, Stephanie Yuan Jiun (Universiti Malaysia Sarawak (UNIMAS), 2015)
Lundu, the study area of this study, shows a continuous increase in the number of hardcore poor even though various types of government-sponsored poverty eradication programmes have been implemented. The objective of this study is to evaluate the impact of government sponsored poverty eradication programmes in Lundu in terms of income, house conditions, health, and literacy status. This study also aims to access the process of implementing government-sponsored poverty eradication programmes in Lundu. Out of 2,961 total population, 150 heads of the households were selected as respondents by using a stratified random sampling technique. Face-to-face interviews with the respondents as well as with the officers-in-charge from the relevant department were carried out to collect the data and related to poverty eradication programmes in this study. The result shows a failure of policy and practice in the government-sponsored poverty eradication programmes. This is because the implementation of this government-sponsored poverty eradication programmes were short term in nature and creating spoon-fed dependent rural poor rather than emphasizing on empowerment when assisting the poor. Policy makers should emphasise on enhancing the knowledge of the poor in basic financial management and acquaint them with relevant skills which are related to their economic activities. This is to ensure that the poor are able to experience capital expansion and achieve self-sustainability as well as independence instead of depending on the assistances given by the government which only provide them with short term relief.